A Rare Case of Metastatic Choriocarcinoma of Lung Origin. (7th December 2017) - Rali, Parth; Xie, Jianwu; Rali, Grishma; Rali, Mayur; Silverman, Jan; Malik, Khalid
Abstract : Choriocarcinoma is part of the spectrum of gestational trophoblastic disease that occurs in women of reproductive age. Although the most common metastatic site of choriocarcinoma is the lung, primary pulmonary choriocarcinoma is rare. To diagnose primary pulmonary choriocarcinoma, the patient should have no previous gynecologic malignancy, have elevated human chorionic gonadotropin, and have pathological confirmation of the disease excluding gonadal primary site of the tumor. Due to the paucity of data, there are no guidelines for treatment. Prognosis of this malignancy is extremely poor. We report a rare case of metastatic primary lung choriocarcinoma in a 69-year-old postmenopausal woman who was treated with combination of surgery, chemotherapy, and radiation. The patient had a good outcome and is doing well after 1-year follow-up.